TAXONOMIC IDENTITY OF ARISAEMA CONDAOENSE (ARACEAE) BASED ON NEW MORPHOLOGICAL AND MOLECULAR DATA - Thien, Van Hong; Nguyen, Phi Nga; Truong, Luu Hong (Vietnam Journal of Biotechnology, 2018)
Arisaema condaoense V.D. Nguyen was described as a new species from Con Dao National Park, Ba Ria–Vung Tau Province, Vietnam in 2000. However, this species has been suspected of being a form of Arisaema roxburghii Kunth, a species widespread in the whole Indochina and Malay Peninsula. This was due to the original description based on dried specimens with male inflorescences only. Morphological characteristics of female inflorescences, which are of taxonomical importance to identify the species, have not been known. In June 2015, we re-sampled the plant in Con Dao National Park with both male and female inflorescences for detailed examination of morphological characteristics. Besides, the matK gene of the chloroplast genome of this species was sequenced to analyse its phylogenetic relationship with other Arisaema species. The gathered morphological and molecular data indicate that A. condaoense is certainly a distinct species, not a synonym of A. roxburghii. The noted morphological characteristics also provide key differences to distinguish A. condaoense from two other morphologically close species of sect. Fimbriata (i.e A. maxwellii from Thailand and A. pierreanum from Vietnam which also share yellow spathes and several other characteristics in common), which are supported by the molecular data. Thus, the species is endemic to Con Dao National Park in Ba Ria–Vung Tau Province, Vietnam. Furthermore, this study allows us revising the description of A. condaoense with, for the first time, supplemental key taxonomic characteristics and illustrating colourful photographs taken from the fresh materials. A key to all eight known Vietnamese species of sect. Fimbriata is also given.